Research on the innovation and path of the business model of live marketing - GUANGYAO LI (Journal of Advanced Research in Social Sciences and Humanities, 2021)
Aim: Live marketing is a result of the interactive integration of new technology and marketing activities in the modern era, and it has emerged as a new business model for network marketing. This research, aims to examine the elements of live marketing’s business model and its potential for future innovation by applying the business model theory, integrating the value creation process.Method: Drawing on the experiences of popular live streaming platforms like Taobao, Tiktok, Jingdong, and Amazon as case studies, and adopted a qualitative study design with content and thematic analysis approach.Findings: (1) The study uncovered that the live marketing model now includes cutting-edge integrations and values. Live marketing thrives when technical systems are integrated with marketing strategies; (2) Live broadcast sellers can be classified as super sellers, famous sellers, ordinary sellers, or low-level sellers based on the anchor’s influence and the audience’s attractiveness. It’s a novel categorization being put forth for the first time, and it makes crucial evaluative contributions to our ability to parse out and comprehend the various types of live broadcasts. This article uses the business model canvas to show how the value proposition is the central fulcrum of a new approach to live marketing’s business model. (4) The path of live marketing’s business model innovation is also the path of value rebuilding, with value growth constituting the crux of BMI’s long-term viability.Implications/Novel Contribution: The new findings can aid non-live broadcast marketers in rethinking their marketing strategies and boosting their sales potential. From the vantage point of the connection between business model innovation and value creation, this research analyzes the dynamics of live marketing and proposes a novel model for its innovation and the process by which it generates value for sellers and buyers. Hence bringing key insights for marketers, scholars and policymakers working in e-business market across the globe.